Efficacy of couselling in STD reference health units in the city of Fortaleza, CE, Brazil - Araújo, Maria Alix L.; Bucher, Júlia S.N.F.; Bello, Pierre Yves (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: STD specificcounselling is part of the national Brasilian strategy for interrupting STD transmission and preventing its complications.Objective: was to assess the efficacy of a STD counselling following national recommendations. This study was design with STD patients seen in outpa-tients department of four referral units of Fortaleza, northeast Brazil. Results: 306 patient were recruited and randomly assigned to the intervention group(STD specific counselling) or control group (no STD specific counselling). Conclusion:people who received STD specific counselling showed betterresults in key issues than people who did not received. They had a better adhesion to treatment (p = 0.0054, OR = 2.49); a better sexual partner notificationand partner treatment (p = 0.0000, OR = 10.96); a better condom use or abstinence during treatment (p = 0.02, OR = 1.84); and a better return to consulta-tion (p = 0.001, OR = 2.09). The study showed that within public health facilities, a concise and specific STD counselling is able to improve results in keyissues for reduction of incidence and prevalence of STD.